1997
DOI: 10.1007/bf03043692
|View full text |Cite
|
Sign up to set email alerts
|

The role of previous cholecystectomy in patients with colorectal cancer

Abstract: Summary. There is a large body of literature which undertakes to look at a possible association between cholecystectomy and colorectal cancer. We set out to conduct a meta-analysis to investigate this. The overall odds ratio for all studies looked at was 1.36 with 95% confidence intervals (CI) 1.07 to 1.74, significant at the 5% level (p = 0.014). The overall odds ratio fora subset of studies deemed "good studies" established by a customised ranking score was 1.66 (1.34 to 2.03), p < 0.0001. The odds ratios fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Several meta-analyses have supported an association between cholecystectomy and colorectal cancer [1][2][3][4][5][6]. Because cholecystectomy is most often indicated for the treatment of gallstone disease [45], it remains unclear whether the increased risk of colorectal cancer in cholecystectomized patients may be due to previous gallstone disease rather than the removal of the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several meta-analyses have supported an association between cholecystectomy and colorectal cancer [1][2][3][4][5][6]. Because cholecystectomy is most often indicated for the treatment of gallstone disease [45], it remains unclear whether the increased risk of colorectal cancer in cholecystectomized patients may be due to previous gallstone disease rather than the removal of the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a large number of conflicting studies exploring the relationship between cholecystectomy and the development of colorectal cancer. Several meta-analyses on this topic suggest a positive correlation [1][2][3][4][5][6]. It has been proposed that the removal of the gallbladder results in a high proportion of carcinogenic secondary bile acids being produced, in particular deoxycholic acid [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses have supported an association between cholecystectomy and colorectal cancer [1][2][3][4][5][6]. As a majority of cholecystectomy is indicated by gallstone disease [91], it remains unclear whether any increased risk of colorectal cancer in cholecystectomized patients may be due to previous gallstone disease rather than the removal of the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have previously demonstrated an association between cholecystectomy and colorectal cancer [1][2][3][4][5][6]. Studies have also indicated that the risk may be the greatest in the proximal colon, though studies contradict this claim [42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 98%